(3eUGObI GdENhGfs - (3Gdbej, GHf HGnHnhrjg, CHh LYaQ, GdUOhb, eMeO Hf Ydj Hf GdMSjf Hf ehSi, J (B381 (3gs ((3gGOj Hf YHGS GdWHGWHGFj GdCUagGfjs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3HGH EfUGa GdENhGf (B: (3MOKfG eMeO Hf jMji GdYWGQ Yf CMeO Hf eMeO Hf YjSi Yf HYV CUMGHfG Yf jhfS Hf YHO GdQMef Yf CHj LYaQ Ydjg GdSdGe bGd bGe Edi CejQ GdeDefjf Ydjg GdSdGe QLd HGdHUQI abGd jG CejQ GdeDefjf (B...s
(3BNQgG (B:s
...(3Yf CHj GdLGQhO Yf CHj YHO Gddg Ydjg GdSdGe bGd jCJj Ydi GdfGS ReGf djS ajg TjA CYR ef CN Ch cSH OQge ef MdGd (B. (3Jes
(3Yf fSNI HNW GdYdGeI GdejQRG eMeO Ydj GdEQOHGOjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\ 274s
(3GdPQjYI (B21\4108s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdMOjK hGdeUWdMs